Dynamic model to predict heat-induced protein denaturation and fouling in a Direct Contact Steam Condensation process. (November 2020) - Safavi Nic, S.S.; Buist, K.A.; Verdurmen, R.E.M.; Kuipers, J.A.M.
Highlights: Reaction kinetic modelling of the formation of a protein rich deposit layer. Dynamic modelling of the sterilization unit including heat and mass transfer. Numerical verification of the model with analytical solutions. Model validation of the heat-exchanger model with experimental data. Abstract: High heat treatment, using Direct Contact Condensation (DCC), is applied in the production of dairy products to ensure a high level of food safety. During this process a protein rich deposit layer can be formed causing fouling of the system resulting in a loss of effective production time and an increase in cleaning cycles. The dynamics of the heat treatment process is modelled, including the description of the pre-heating step with two laminar flow tubular heat-exchangers followed by a DCC. In this system the bulk reactions for whey proteins are modelled using unfolding, re-folding and aggregation kinetics. The formation of the deposit layer is described in the segment after the DCC using a flow averaged model incorporating diffusion of species through the mass boundary layer as well as adsorption to the wall and desorption from the wall. The desorption kinetics are key as the protein deposit layer releases from the wall once the wall friction increases due to the decreasing area available for throughflow. The model shows good agreement with experimental data and is capable of capturing the process dynamics, both for the heat exchanger and the DCC. The deposit layer formation model is in agreement with the trend observed in the experimental data but is not fully capturing the process dynamics.